Comparative Evaluation of Microleakage and Compressive Strength of Different Restorative Materials – An in vitro Study - Hetal Khuva; Deepak Kurup; Shazia Mahreen; Srishti; Trina Mukherjee; Sourav Tikadar (Journal of Pharmacy and Bioallied Sciences)
Background: For dental restorations to be successful in clinical practice, they must possess excellent mechanical properties, such as high compressive strength and microleakage resistance. Materials and Methods: A total of 80 Class V cavities were prepared from extracted human teeth, divided into four groups of 20 (Groups A, B, C, and D). One of the following restorative materials Neo–Spectra ST, Activa Bioactive Material, SDR Bulkfill Flowable Composite, or Zirconomer was used to restore each group. Standardized testing procedures were used to evaluate compressive strength, and dye penetration techniques were used to measure microleakage. ANOVA and Tukey’s post hoc test, were two of the statistical procedures used to compare the performance of the various materials. Results: Neo Spectra ST had the lowest average microleakage score of 0.5 mm, which was significantly lower compared to Activa Bioactive Material at 1.2 mm, SDR Bulkfill Flowable Composite at 0.8 mm, and Zirconomer at 1.5 mm. In terms of compressive strength, Neo Spectra ST showed the highest average value at 120 MPa, with SDR Bulkfill Flowable Composite following at 100 MPa, Activa Bioactive Material at 80 MPa, and Zirconomer at 60 MPa. Statistical analysis showed significant variations in both microleakage and compressive strength between the materials (P < 0.05), highlighting Neo Spectra ST’s excellent performance. Conclusion: Amongst all materials, Neo Spectra ST demonstrated the greatest compressive strength and microleakage resistance compared to Zirconomer, SDR Bulkfill Flowable Composite, and Activa Bioactive Material.